Fabrication and Characterization of Low Voltage Thin Film Transistor using Graphene and Metal Oxide Semiconductor - Chourasia, Nitesh Kumar (IIT BHU, 2020)
Modern display technology requires higher resolution, wide area, mechanical flexibility, optical transparency, and lower cost. Over time enormous size cathode ray tube (CRO) based display has been replaced by an active matrix light-emitting display (AMLED) based display. Active matrix display and Passive matrix display are the two main types of flat panel display technology. Up to the present time, active-matrix flat panel displays (AM-FPDs) have conquered the bigger market and that has been developed as an active matrix thin film transistor (TFT) since 1995. The flat panel LED-based display is thin, lightweight and has the ability to produce high-resolution images which are very useful in many application such as television, monitors, smartphones, laptops, and the portable device. TFTs are the backbone of active matrix display technology and works as a driver (switching device) to drive a pixel in display ‘on’ (light) or ‘off’ (dark), therefore, development of low-cost TFT is urgently required. Because of their high carrier mobility and easy manufacturing process, metal oxide TFT may be one ideal choice for this application. In 1940, Bell Telephone Laboratories demonstrated the first working example of a transistor while Weimer at RCA Laboratories recognized the first working thin-film transistor (TFT) in 1962. [1-3] Thin film transistors are basically three-terminal metal oxide field effect transistor devices. In a TFT structure, the dielectric layer is sandwiched between the gate electrode and the semiconductor. The charge flow through the semiconducting layer between the source and drain electrodes can be modulated by the gate bias, which induces polarization in the dielectric layer. Thin-film transistors are constructed using three main components; namely, i) a dielectric layer, ii) a semiconducting material, and iii) metallic electrodes (source (S), drain (D) and gate (G)). Dielectric, active channel layer, and their manufacturing process play a very important role in the performance of thin-film transistors.[4] There are various vacuum-based techniques for making thin-film transistors,e.g.,sputtering, molecular beam epitaxy (MBE), chemical, and atomic vapor depositions.[5-7] While the use of vacuum-based technology can deposit high quality of thin films, these techniques are cost capital and complex. An alternative approach is solution process techniques, which are very simple, convenient, and cost-saving. Solution-processed MOx dielectric materials have been widely studied due to their high-k values[8-10], excellent optical transparency[11, 12], and chemical/environmental stability.[13, 14] Moreover, their main function as a gate dielectric layer in TFTs, high-k dielectrics also plays a very crucial role in the capacitor and memory devices.[15] In this concern, SiO2 is the standard gate dielectric because it makes high-quality film without defect (free from the pinhole, impurity) in the form of native oxide with silicon substrates, which is easily deposited through thermally grown.[16] SiO2, having nearly perfect properties for a gate insulator: high bandgap and electrical resistivity, outstanding Si-SiO2 interface, least defect density in bulk, and high crystallization temperature. However, one main drawback of this dielectric is its lower dielectric constant (k), and due to this issue, metal oxide thin film transistor requires high operating voltages that limit its application to low power electronics. Relatively, high-k AlOx [17] dielectric are batter choice for oxide electronics has been prepared by using various aluminum sources such as aluminum nitrate [18, 19] aluminum acetylacetonate[20], aluminum chloride. Zirconium (ZrOx)[21] and hafnium oxides (HfOx)[22] constitute another class of most-studied high-k oxide dielectrics those are used for low voltage TFT. Subramanian and co-workers reported high-performance all solution-processed MOx electronics using these high -k dielectrics[23]. Alternatively, Katz[24] and co-workers proposed a novel approach by incorporating ionic dopants into MOx lattices to enhance the k value of host dielectric material dramatically.[25, 26]. However, processing temperature of this ionic dielectric is very high (>800o C) which is required to lower significantly for flexible electronics. Moreover, this ionic dielectric is mostly studied for n-channel TFT fabrication. Although for common electronics application, we need both n-channel and p channel TFT. Therefore, development of low voltage p-channel TFT is also required.
Keywords: Fabrication; Voltage; Transistor; Graphene; Semiconductor